2021
DOI: 10.1039/d1qi00799h
|View full text |Cite
|
Sign up to set email alerts
|

Tandem-like vanadium cluster chains in a polyoxovanadate-based metal–organic framework for efficient catalytic oxidation of sulfides

Abstract: A novel polyoxovanadate-based metal‒organic framework (POV-MOF), [Ni(bix)2]{V4O11} (V-Ni-MOF, bix = 1,4-bis(imidazol-1-ylmethyl)benzene), was successfully synthesized and structurally characterized. Single crystal X-ray diffraction analysis shows that the {V4} clusters in V-Ni-MOF are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 59 publications
2
27
0
Order By: Relevance
“…Moreover, considering the selectivity of MPSO, TOF and the O/S ratio, the catalysts we synthesized, especially catalyst 1, are superior to most of the catalytic systems that have been reported thus far (Tables 1 and S4 †). [51][52][53][54][55][56][57][58] This series of comparative results suggested that designing porous frameworks with more efficient mass transfer channels and as many exposed active sites as possible may be an efficient strategy by which to build more powerful catalysts.…”
Section: Structural Description Of Compoundmentioning
confidence: 99%
“…Moreover, considering the selectivity of MPSO, TOF and the O/S ratio, the catalysts we synthesized, especially catalyst 1, are superior to most of the catalytic systems that have been reported thus far (Tables 1 and S4 †). [51][52][53][54][55][56][57][58] This series of comparative results suggested that designing porous frameworks with more efficient mass transfer channels and as many exposed active sites as possible may be an efficient strategy by which to build more powerful catalysts.…”
Section: Structural Description Of Compoundmentioning
confidence: 99%
“…Currently, the further development of POMOF catalysts requires a deep understanding of their catalytic mechanisms, which is important for guiding the structural design and functional optimization of POMOF catalysts. [42][43][44] Herein, for achieving a highly efficient catalyst for the oxidation of benzylic C-H bonds and a suitable model for mechanistic studies, we constructed a novel polyoxovanadatebased MOF, [Cu I 2 Cu II (bix) 2 ]{V 4 O 12 } (1, bix ¼ 1,4-bis(imidazole-1-ylmethyl)benzene). The structure of 1 contains three possible active centers in close proximity, V V in the highly oxidized state in the unique U-type {V 4 } cluster, Cu I with redox ability and Cu II with coordination unsaturation.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the further development of POMOF catalysts requires a deep understanding of their catalytic mechanisms, which is important for guiding the structural design and functional optimization of POMOF catalysts. 42–44…”
Section: Introductionmentioning
confidence: 99%
“…Polyoxovanadates (POVs), as a prominent branch of polyoxometalates (POMs) with well-defined architectures and versatile physicochemical properties, have been investigated in the fields of catalysis, 1–3 molecular magnetism, 4,5 energy storage, 6,7 biomedicine, 8 etc. Compared with the extensive literature on polyoxomolybdates and polyoxotungstates, a relatively few studies have been concentrated on POVs.…”
Section: Introductionmentioning
confidence: 99%